The Political Economy of Social Accountability in Nepal - Tamang, Seira (World Bank, Washington, DC, 2014)
The World Bank has introduced a new Program for Accountability in Nepal (PRAN) to enhance the capacities of civil society and government actors to utilize social accountability approaches and tools. This political economy study seeks to inform the PRAN by identifying the strengths and opportunities as well as risks and obstacles for social accountability initiatives in Nepal. It includes recommendations for managing and addressing these issues. The study is based on primary and secondary research conducted from September 2010 to February 2011. The research methodology utilized for this study was three-fold. First, a literature review was undertaken including in-country laws, policies and regulations, as well as a range of studies and articles on issues of relevance to social accountability in Nepal. A bibliography of these materials is attached as annex one. Second, semi-structured interviews were conducted with key civil society leaders, non-governmental organization (NGO) staff, journalists, academics, government officials, and citizens. A list of people interviewed and guiding questions are attached as annex two. Third, the research team made field visits to the eastern and western regions of the country to observe social accountability initiatives and interview local stakeholders. In total 75 people were interviewed, including 12 civil society leaders. Focus group discussions with citizens were also conducted in Ilam, Dhankuta, Itahari, and Palpa. The first section of the paper provides a brief historical overview of political development in Nepal, and highlights how these historical legacies influence current day citizen-state relations and accountability relationships. Section two analyzes the legislative and institutional framework for social accountability in Nepal. The third section of the paper analyzes a range of contextual factors influencing social accountability in Nepal. Section four identifies citizen information, citizen voice, and collective action as three key elements of social accountability in Nepal, and discusses current strengths and weaknesses with regard to each of them. Section five of the paper looks at each one of the PRAN's three focal areas - public financial management, municipal governance, and community-based monitoring and evaluation of public services. Finally, section six outlines conclusions and recommendations for promoting social accountability in Nepal.